FINANCIAL PROBLEMS OF UZBEKISTAN ECONOMY DEVELOPMENTFINANCIAL PROBLEMS OF UZBEKISTAN ECONOMY DEVELOPMENT - BOBAKULOV TULKIN IBODULLAEVICH (International journal of economic perspectives, 2022)
Solving the current problems related to ensuring the stability of the country’s financial system is one of the necessary conditions for ensuring the stable development of the national economy. Issues such as preventing the growth of inflation, ensuring the stability of the national currency, achieving the proportionality of the execution of the state budget, and increasing the level of the economy’s supply of money are the urgent financial issues of ensuring the stability of the country’s economy. In the article, the current financial problems of the development of the economy of Uzbekistan are identified and scientific proposals aimed at solving them are developed.